An Approach to Mitigate Blackhole Attack on Delay Tolerant Networks using Multiple Paths (Research, Society and Development, 2020)
Delay and Tolerant Networks (DTNs) are networks that do not need infrastructure and use their nodes to communicate. However Blackhole attacks (Blackhole) constitute a threat to the functioning of these networks by dropping packets from legitimate users. There are attempts in the literature to solve the blackhole attack on DTNs. However, the implemented forms consume a large amount of network resources because they work by generating copies of the message. This paper presents a Mitigation approach that uses Mojette and multiple paths to fragment, send and retrieve data without high network wear. The approach was developed using the Eclipse IDE in conjunction with The Opportunistic Network Environment Simulator. In this environment two scenarios with different situations were developed in order to perform three simulations, aiming to evaluate the approach that aims to transmit and retrieve the package even if there are discards.  Simulation results show that the approach has a re-assembly rate of at least 75%, even though the lost packet rate is 62.50%.